68Ga PET Imaging in Patients With Neuroendocrine Tumors: A Systematic Review and Meta-analysis. (November 2018) - Singh, Simron; Poon, Raymond; Wong, Rebecca; Metser, Ur
Abstract : Purpose: The aim of this study was to systematically review the literature to assess the role of 68 Ga PET imaging in neuroendocrine tumors (NETs). Materials and Methods: The literature was searched using MEDLINE, EMBASE, and Cochrane Database of Systematic Reviews databases through OVID. Studies comparing PET or PET/CT with conventional imaging in the initial diagnosis, staging and restaging, assessment of treatment response, and routine surveillance of NETs were deemed eligible for inclusion. Risk of bias and applicability concerns were assessed using the Quality Assessment of Diagnostic Accuracy Studies tool. Results: Twenty-two studies met the inclusion criteria. For the initial diagnosis of NETs, PET or PET/CT had a pooled sensitivity of 91% (95% confidence interval [CI], 85%–94%) and a pooled specificity of 94% (95% CI, 86%–98%). In the setting of staging and restaging, the sensitivity of PET or PET/CT for detecting primary and/or metastatic lesions ranged from 78.3% to 100%, whereas specificity ranged from 83% to 100%. Change in management occurred in 45% (95% CI, 36%–55%) of the cases, with majority of the changes involving surgical planning and patient selection for peptide receptor radionuclide therapy. Conclusions: 68 Ga PET or PET/CT is recommended for initial diagnosis where conventional testing remained equivocal, for staging of patients with localized primary and/or limited metastasis where definitive surgery is planned, to determine somatostatin receptor status and suitability for peptide receptor radionuclide therapy, and for staging of patients where detection of occult disease will alter treatment options and decision making.